Psychosocial Work Conditions During the COVID-19 Pandemic and Their Influences on Mental Health Risk and Intention to Leave Among Public Health Workers: A Cross-sectional and Follow-up Study in Taiwan - Ming-Wei Lin; Yi-Ting Wang; Yawen Cheng (Elsevier, 2023)
Background: To examine the influences of psychosocial work conditions on mental health risk and intention to leave the public sector among workers of public health agencies in Taiwan. Methods: We surveyed 492 public health workers in March 2022 during the COVID-19 pandemic. Information on job demands, job control, workplace justice, experiences of workplace violence and its type and origin, and mental health status (assessed by the 5-item Brief Symptom Rating Scale, BSRS-5) was obtained. Of them, 192 participated in a follow-up survey conducted in May 2023 that assessed mental health status, employment changes, and intention to leave. Results: In the initial survey, 32.93% of participants reported poor mental health status, defined by having a score of BSRS-5 ≧ 10, and 48.17% experienced some form of workplace violence over the past year. Notably, high psychosocial job demands (OR = 3.64, 95% CI = 1.93-6.87), low workplace justice (OR = 2.58, 95% CI = 1.45-4.58), and workplace violence (OR = 2.38, 95% CI = 1.51-3.77) were significantly associated with increased risk of mental disorders. Among those who participated in the follow-up survey, 22.40% had persistent poor mental health, and 30.73% considered leaving or have left the public sector. Longitudinal analyses indicated that job demands predicted persistent mental disorders and intention to leave the public sector, and the experience of workplace violence added additional mental health risks. Conclusion: The public health workforce is crucial for effective and resilient public health systems. Our findings that public health workers were at high mental health risk and had a high intention to leave the job warrant attention and policy interventions.